Penerapan Metode Keteladanan Guru Akidah Akhlak Dalam Membentuk Sikap Tawadhu’ Siswa - Syaikhu, Ach; Putri, Siska Eka (AS-SUNNIYYAH, 2024)
This research is motivated by negative student behaviors at MTS AL Haromain Mojosari, such as disrespecting teachers, disobedience, sleeping in class, skipping school, and leaving the class before the teacher. The aim of this study is to describe the implementation of the exemplary method by Akidah Akhlak teachers in cultivating the attitude of tawadhu' (humility) in students towards Allah, the Prophet Muhammad, and fellow believers. This study uses a qualitative method with observation, interviews, and documentation techniques. The results show that the exemplary method successfully cultivated students' tawadhu' towards Allah and the Prophet Muhammad, but for tawadhu' towards fellow believers, further habituation is needed.